Security Enhancement of IoT and Fog Computing Via Blockchain Applications - T. H. Hasan, Ramadan; Y. Ameen, Siddeeq (Journal of Soft Computing and Data Mining, 2021)
Blockchain technology is now becoming highly appealing to the next generation because it is better tailored to the information age. Blockchain technologies can also be used in the Internet of Things (IoT) and fog computing. The development of IoT and Fog Computing technologies in different fields has resulted in a major improvement in distributed networks. Blockchain technology is now becoming highly appealing to the next generation because it is better tailored to the information age. Blockchain technologies can also be used in IoT and fog computing. The blockchain principle necessitates a transparent data storage mechanism for storing and exchanging data and transactions throughout the network. In this paper, first, we explained Blockchain, its architecture, and its security. Then we view Blockchain application in IoT security. Then we explained Fog computing, Generic Security Requirements for Fog Computing, and we also discuss Blockchain applications that enhance Fog Computing Security. Finally, we conduct a review of some recent literature on using Blockchain applications to improve the security of IoT and fog computing and a comparison of the methods proposed in the literature.